In Vitro Regeneration of Vitex negundo L., a Woody Valuable Medicinal Plant through High Frequency Axillary Shoot Proliferation - Afroz, Farhana; Hassan, AKM Sayeed; Bari, Laila Shamroze; Sultana, Rebeka; Munshi, John Liton; Jahan, Miskat Ara Akhter; Khatun, Rahima (Bangladesh Journal of Scientific and Industrial Research, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> An efficient protocol was established for rapid and large scale propagation of woody aromatic medicinal plant Vitex negundo L. by in vitro shoot multiplication from shoot tips and nodal segments of mature plant. Of the four different growth regulators BA, Kn, GA3, NAA and coconut water, MS fortified with BA 1.0 mg/l was found to be the most effective for inducing multiple shoots from nodal explants. The percentage (96%) of shoot multiplication per node (21.83) was highest up to second subculture passages, after which there was a gradual decline in shoot development. Best rooting was induced (93%) in excised shoots on half strength MS medium supplemented with an optimal combination of NAA (0.3 mg/l). Soil, compost and sand (1:1:1) mixture was the most suitable planting substrate for hardening. The survival rate was 80% and the regenerated plants were successfully transferred to the soil. Key words: Vitex negundo, Medicinal plant, Shoot proliferation, Micropropagation, Regeneration DOI = 10.3329/bjsir.v43i3.1149 Bangladesh J. Sci. Ind. Res. 43(3), 345-352, 2008